NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI DAN RELEVANSINYA SEBAGAI BAHAN AJAR BAHASA INDONESIA - Widyanto, Danik Ary; Yuliantoro, Agus; Sukini, Sukini; Hersulastuti, Hersulastuti (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This study is motivated by the urgency of strengthening character education in junior high school literature learning, which has not optimally utilized literary works as a medium for internalizing values, resulting in a gap between curriculum objectives and classroom practices that remain cognitively oriented. The study aims to describe the character education values contained in the novel Negeri 5 Menara by Ahmad Fuadi and to analyze its relevance as an alternative teaching material for eighth-grade novel text learning. This research employs a descriptive qualitative approach using content analysis. The primary data consist of the novel text, while supporting data are derived from curriculum documents. Data were collected through intensive reading and note-taking, then analyzed through data reduction, data display, and conclusion drawing, strengthened by document triangulation. The findings reveal values of religiosity, discipline, hard work, responsibility, honesty, independence, appreciation of knowledge, and friendship, which align with the basic competencies of novel text learning and support the development of students’ character profiles. The study concludes that integrating literary works enriches literacy experiences and fosters contextual character formation, making the novel relevant and appropriate as teaching material in literature learning. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya penguatan pendidikan karakter dalam pembelajaran sastra di SMP yang belum optimal memanfaatkan karya sastra sebagai media internalisasi nilai, sehingga terjadi kesenjangan antara tujuan kurikulum dan praktik pembelajaran yang masih berorientasi kognitif. Penelitian bertujuan mendeskripsikan nilai-nilai pendidikan karakter dalam novel Negeri 5 Menara karya Ahmad Fuadi serta menganalisis relevansinya sebagai alternatif bahan ajar teks novel kelas VIII SMP. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode analisis isi. Data berupa teks novel sebagai sumber utama dan dokumen kurikulum sebagai pendukung, dikumpulkan melalui pembacaan intensif dan pencatatan, lalu dianalisis melalui reduksi, penyajian, dan penarikan simpulan dengan penguatan triangulasi dokumen. Hasil menunjukkan adanya nilai religiusitas, disiplin, kerja keras, tanggung jawab, kejujuran, kemandirian, apresiasi terhadap ilmu, dan persahabatan yang selaras dengan kompetensi dasar pembelajaran teks novel serta mendukung profil pelajar berkarakter. Temuan menegaskan bahwa integrasi karya sastra dapat memperkaya literasi sekaligus membentuk karakter secara kontekstual, sehingga novel tersebut relevan dan layak digunakan sebagai bahan ajar dalam pembelajaran sastra.